2013
DOI: 10.3109/01676830.2013.764449
|View full text |Cite
|
Sign up to set email alerts
|

IgG4 Orbital Inflammation in a 5-Year-Old Child Presenting as an Orbital Mass

Abstract: IgG4 is a newly known systemic disorder. It can present as orbital inflammation or as an orbital mass. We describe the case of a 5-year-old child with proptosis and globe dystopia who went on to have an orbital biopsy. Initially this was reported to be idiopathic orbital inflammation. After IgG4-RD was considered in the differential, the orbital biopsy was revisited, immunohistochemistry was done and the patient's serum was tested for IgG subclass levels. IgG4-RD was diagnosed and the patient was subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“… Griepentrog 2013 [ 7 ] 14y F IgG4-ROD H+ N (L U) Pred, dosage unknown, and MMF MMF because of relapse after tapering pred, successful. Kalapesi 2013 [ 10 ] 5y F IgG4-ROD H+ El (1.52 g/l) Pred 1 mg/kg and MMF (600 mg/m2) Weaned off pred and maintained on MMF successfully. Naghibi 2013 [ 15 ] 16y F IgG4-related colitis, in the past AIP-1 H+ El (210 mg/dl) Adalimumab Refractory disease to pred 0.5 mg/kg, Aza and infliximab.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Griepentrog 2013 [ 7 ] 14y F IgG4-ROD H+ N (L U) Pred, dosage unknown, and MMF MMF because of relapse after tapering pred, successful. Kalapesi 2013 [ 10 ] 5y F IgG4-ROD H+ El (1.52 g/l) Pred 1 mg/kg and MMF (600 mg/m2) Weaned off pred and maintained on MMF successfully. Naghibi 2013 [ 15 ] 16y F IgG4-related colitis, in the past AIP-1 H+ El (210 mg/dl) Adalimumab Refractory disease to pred 0.5 mg/kg, Aza and infliximab.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, despite the presence of IgG4 positive plasma cells in the tissue, two case reports concerning Rosai-Dorfman disease and ALK-1 positive inflammatory myofibroblastic tumor [ 22 , 23 ] were excluded, because according to Boston consensus these diseases should not be considered as IgG4-RD. Serum IgG4 was measured in 23 of the 25 cases, and was found to be elevated in 16 cases [ 5 , 6 , 8 , 10 , 12 , 14 – 19 , 24 27 ] (70 %).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until September 2017, to the best of our knowledge, 13 cases -10 females and 3 males-of children with ophthalmic manifestations have been described [13][14][15][16][17][18][19][20][21][22]. The most common symptomatology was unilateral protrusion/swelling (11/13, 84.6%), while eyelid involvement was also mentioned in 6/13 (46.1%) cases (Table-1 Serum IgG4 levels were found to be increased in 5/13 (38.5%) of the patients, inflammation markers in 3/6 (50%), while autoimmune profile was negative in all the patients for whom data were available (Table-1) Clinical findings and imaging studies, in these patients, suggested "orbital mass" as the most common finding.…”
Section: Paediatric Populationmentioning
confidence: 99%
“…20 The mean age of onset for IgG4-ROD is 55.5 years (SD 12.9), slightly younger than for AIP, at somewhere between 58 and 69 years. [22][23][24][25] In 2 Japanese studies, patients with AIP had lacrimal and salivary gland lesions in 39% and 47.5%, 26,27 but a third Japanese study looking at 56 AIP patients found extrapancreatic lesions synchronously in 18, and metachronously in 18 (the AIP followed the other lesions), but only 2 of these were lacrimal gland lesions, and 8 were salivary gland lesions. [22][23][24][25] In 2 Japanese studies, patients with AIP had lacrimal and salivary gland lesions in 39% and 47.5%, 26,27 but a third Japanese study looking at 56 AIP patients found extrapancreatic lesions synchronously in 18, and metachronously in 18 (the AIP followed the other lesions), but only 2 of these were lacrimal gland lesions, and 8 were salivary gland lesions.…”
Section: Epidemiologymentioning
confidence: 99%